Conditional Cash Transfers, Political Participation, and Voting Behavior - Baez, Javier E.; Camacho, Adriana; Conover, Emily; Zárate, Román A. (World Bank, Washington, DC, 2013)
This paper estimates the effect of enrollment in a large scale anti-poverty program in Colombia, Familias en Accion, on intent to vote, turnout and electoral choice. For identification the analysis uses discontinuities in program eligibility and variation in program enrollment across voting booths. It finds that Familias en Accion had a positive effect on political participation in the 2010 presidential elections by increasing the probability that program beneficiaries registered to vote and cast a ballot, particularly among women. Regarding voter's choice, the authors find that program participants expressed a stronger preference for the official party that implemented and expanded the program. Overall, the findings show that voters respond to targeted transfers and that these transfers can foster support for incumbents, thus making the case for designing political and legislative mechanisms, as the laws recently passed by the Colombian government, that avoid successful anti-poverty schemes from being captured by political patronage.